Case Study of The Supreme Court Ruling Number: 3002 K/Pdt/2015 On The Validity of Provision of Income Agreement Which Was Made Before Divorce Based On Civil Code - Kusmayanti, Hazar; Warapsari, Tri Utami; Rachmainy, Linda (Jurnal Cita Hukum, 2019)
Abstract:A legally created agreement applies as law to those who make it. The terms of the validity of an agreement are regulated in Article 1320 of the Civil Code (KUHPerdata). If the terms of the validity of the agreement are not fulfilled, then the legal consequences arising from such agreements can be annulled or null and void. The practice in society can be seen in The Supreme Court Ruling Number 3002 K/PDT/2015, there was married couple who are while in the period of marriage bonds, made agreements in front of the Notary and written down in Notarial Deed Number 72, which content is concerning the demand of child’s living cost for a lifetime, asked by the wife to the husband when the divorce happens later. The Supreme Court Ruling Number 3002 K/PDT/2015 states that the demand of living cost agreement is invalid and can be annulled because it does not meet one of the requirements of the validity of the agreement, which is the lawful reason as regulated in Article 1320 of the Civil Code. The purpose of this study is to know the Supreme Court Ruling on the validity of the demands of living cost agreement and legal consequence of the agreement based on the Civil Code.Keywords: the validity of the demands of living cost agreement, the legal consequence of the agreement Abstrak:Suatu perjanjian yang dibuat secara sah berlaku sebagai undang-undang bagi mereka yang membuatnya. Syarat-syarat sahnya suatu perjanjian diatur dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata (KUHPerdata). Apabila syarat-syarat sahnya perjanjian tidak terpenuhi, maka akibat hukum yang ditimbulkan adalah perjanjian tersebut dapat dibatalkan atau batal demi hukum. Dalam praktek di masyarakat sebagaimana yang ada pada Putusan Mahkamah Agung Nomor 3002 K/PDT/2015, terdapat pasangan suami istri yang dalam masa ikatan perkawinan membuat perjanjian di hadapan Notaris dan dituangkan di dalam Akta Notaris Nomor 72, isinya menyangkut tuntutan nafkah hidup untuk anak dan dimintakan selama seumur hidup yang diajukan oleh istri kepada suami apabila kelak terjadi perceraian. Putusan Mahkamah Agung Nomor 3002 K/PDT/2015 menyatakan bahwa perjanjian tuntutan nafkah tersebut tidak sah dan dapat dibatalkan karena tidak memenuhi salah satu syarat sahnya perjanjian yaitu syarat sebab yang halal yang diatur di dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata (KUHPerdata). Tujuan penelitian ini adalah untuk mengetahui putusan Mahkamah Agung tentang keabsahan perjanjian tuntutan nafkah dan akibat hukum perjanjian tersebut ditinjau dari Kitab Undang-Undang Hukum Perdata (KUHPerdata).Kata Kunci: Keabsahan Perjanjian Tuntutan Nafkah, Akibat Hukum Perjanjian Аннотация:Законно созданное соглашение применяется как закон к тем, кто его делает. Условия действия договора регулируются статьей 1320 Гражданского кодекса (KUHPerdata). Если условия действия соглашения не выполнены, то юридические последствия таких соглашений могут быть аннулированы или признаны недействительными. Практику в обществе можно увидеть в Постановлении Верховного суда № 3002 K / PDT / 2015: была супружеская пара, которая находилась в период брачных уз, заключила соглашения с нотариусом и записала в нотариальном акте № 72, какое содержание касается потребности в стоимости жизни ребенка на всю жизнь, которую жена спрашивает у мужа, когда развод происходит позже. Постановление Верховного суда № 3002 K / PDT / 2015 гласит, что соглашение о стоимости жизни недействительно и может быть аннулировано, поскольку оно не соответствует одному из требований срока действия соглашения, что является законной причиной, регулируемой статьей 1320 Гражданского кодекса. Цель данного исследования состоит в том, чтобы узнать постановление Верховного суда об обоснованности требований соглашения о стоимости жизни и правовых последствиях соглашения, основанного на Гражданском кодексе.Ключевые Слова: Обоснованность Требований Договора Прожиточного Минимума, Юридические Последствия Договора